Considerations regarding the evolution, distribution and dynamics of the romanian football (League I) between 1989 - 2016 - Grigore Vasile HERMAN; Sorin D. BUHAȘ; Lucian STANCE; Anca-Cristina POP (Editura Universităţii din Oradea, 2016)
The present study aims to highlight different issues related to: the evolution, repartition and dynamics of the Romanian football (League I) between 1989 - 2016 by using an analytical approach, from singular to particular, from the team (seen as a basic cell in football) to location, county, development regions, historical region and country (seen as administrative units that support football). The importance of the study emerges from the explanatory and logical approach, from the mechanisms that contributed to the development and consolidation of the Romanian football (League I), in close correlation with the postcommunist socio-economic transformations which have defined each administrative unit involved as part of the Romanian national state.